PENGEMBANGAN KREATIVITAS DALAM PEMBELAJARAN MATEMATIKA MELALUI PELATIHAN PEMBUATAN GELANG PADA SISWA SMP DI DESA TIMBANG LAWAN - Fahira Iramadhania; Ila Nazila; Syasya Aisyah; Ahmad Al Hafiz Sagala; Reflina Reflina (CV. Denasya Smart Publisher, 2025)
This research aims to develop students' creativity through bracelet-making exercises that are integrated into mathematics learning which is useful for increasing students' understanding of geometric concepts and patterns. This is a form of skills activity so that students are free to be creative so they are interested in learning mathematics. The research method used is a descriptive qualitative approach where students are given the freedom to design and make bracelets according to their creative ideas. The participants in this research were 9 junior high school students in Timbang Lawan Village. Students are taught how to make bracelets using direct mathematical concepts in determining the pattern, shape and length of rope used. Data was collected through observation, interviews and documentation of students' work from bracelet making training. The research results show that bracelet makers can integrate in increasing students' understanding of geometric concepts and mathematical patterns. Apart from that, with bracelet training students become motivated and interested in learning mathematics